Are Modern Day Marketers Indulging in Cultural Genocide by Changing Consuming Pattern? - Venkatesh, Ramaswami (Indian Journal of Marketing, 2012)
Culture has been one of the vital ingredients in promoting and establishing products in segmented territories. Due to the unrestricted movement of population from different sides, the local and the host population have found it difficult to keep their own cultural habits intact. The unabashed mixture of habits among the younger generation, resulting in consumption of products not specific to cultures have created an opportunity for marketers to borrow product ideas from all cultures and start marketing products, which belong to no one culture in particular. This has given rise to a situation where consumers are easily falling prey to these wile marketers’ attempts to transform a pure culture into a mixed culture and are thereby, indulging in the genocide of one or more cultures. The paper, "Are Modern Day Marketers Indulging In Cultural Genocide By Changing Consuming Pattern?" attempts to verify whether consumers really fall for the marketers’ tactics, or while experimenting with the products on offer, they tend to protect and maintain their own cultural habits.